2010
DOI: 10.1111/j.1743-6109.2010.01829.x
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin Transporter Null Mutation and Sexual Behavior in Female Rats: 5-HT1A Receptor Desensitization

Abstract: Introduction Serotonin plays a key role in sexual behavior. In serotonin transporter (SERT) knockout rats (−/−), basal extracellular 5-HT levels are considerably increased, indicating a serotonergic disturbance. Heterozygous SERT(+/−) rats express 50% of SERT in comparison to wild-type rats and may therefore model the s/s phenotype of the human SERT promoter (5-HTTLPR) polymorphism. Aim In the present study, we used both homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 49 publications
5
25
0
Order By: Relevance
“…Based on the fact that the role of 5-HT 1A receptors is different in females, it could be that 5-HT 1A receptor desensitization in women just prevents sexual side effects. This hypothesis is in line with the findings in our previous study with SERT knockout rats [18].…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…Based on the fact that the role of 5-HT 1A receptors is different in females, it could be that 5-HT 1A receptor desensitization in women just prevents sexual side effects. This hypothesis is in line with the findings in our previous study with SERT knockout rats [18].…”
Section: Introductionsupporting
confidence: 93%
“…One week was used as washout period to prevent accumulation. The doses of (±)8‐OH‐DPAT and WAY‐100635 were based on our previous study performed in wild‐type and SERT knockout rats on the same background strain [18]. WAY‐100635 alone was not tested this time because it did not show any effects on female sexual behavior in previous studies [18].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with this is a recent report that systemic treatment with 8-OH-DPAT reduced proceptivity and also reduced the time females spent in the male’s compartment in a pacing paradigm (Snoeren et al, 2010; Snoeren et al, 2011a; Snoeren et al, 2011b). Because both effects were attenuated by the 5-HT 1A receptor antagonist, WAY100635 (Snoeren et al, 2010; Snoeren et al, 2011b), a 5-HT 1A receptor-mediated effect was implicated. Therefore, the collective findings indicate that 5-HT 1A receptor agonists may negatively affect both consummatory and appetitive/precopulatory effects of female sexual behavior and most evidence is consistent with a location of the relevant receptors that is postsynaptic to 5-HT neurons.…”
Section: 0 Drugs Acting At 5-ht Receptorssupporting
confidence: 88%
“…In addition, since 8-OH-DPAT inhibits sexual behavior in rats that are missing the serotonin transporter (Olivier et al, 2011; Snoeren et al, 2010), the drug’s ability to produce inhibition does not appear to be dependent on changes in reuptake of 5-HT. However, in a recent study with marmoset monkeys, 16 weeks of treatment with 8-OH-DPAT was reported to increase mRNA for the serotonin transporter in the DRN (Aubert et al, 2013).…”
Section: 0 Drugs Acting At 5-ht Receptorsmentioning
confidence: 99%